Turn coat [large type] : a novel of the Dresden files - Butcher, Jim, 1971- (Butcher, Jim, 1971- Dresden files, 2009)
Harry must uncover a traitor within the Wizards of the White Council, keep a less-than-agreeable warden under wraps, and avoid coming under scrutiny himself. And a single mistake may cost someone his head--someone like Harry.